BUSINESS COMMUNICATION STRATEGY OF DPP HIPMIKINDO - JAKARTA IN IMPROVING HUMAN RESOURCE OF JABODETABEK MSMES - Agus Jatmika; Harmonis Harmonis (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The management of Hipmikindo, which consists of people with high business perspectives, is certainly well aware that the resources of MSME entrepreneurs are still uncompetitiveness. The culture of small entrepreneurs who are very pragmatic, looking at business as just a matter of selling, certainly becomes an obstacle to progress and develop “capacity building”. Even more, if the use of technology is responded as a "burden", it becomes a challenge of Hipmikindo’s communication strategy. Consequently, they must implement an effective model to increase the ability and the capacity of its members. This research was conducted from February to June 2020. Data collection technique was used in-depth interviews, which are largely used unstructured patterns, although the guidelines remain; followed by literature study. The objective is to find out Hipmikindo's business communication strategy in increasing the human resources of MSME entrepreneurs as well as supporting and inhibiting factors in implementing the forms of business communication strategy. There are development and dynamics of strategy in the initial and final actions, including the message management strategy. The research method is descriptive qualitative. This choice relates to the research facts that the author found a holistic set of business communication strategies that cannot be partially understood. The results show that the dynamics of Hipmikindo’s business communication strategy in increasing the resources of MSMEs in Jabodetabek involves several terms. At first, the pull model is used, then the push. Pull, by accommodating all the aspirations and inspiration of the SMEs to find a solution, while “push” includes: 1) communication strategies for change. 2) “S” cycle message management strategies, 3) quoting the concept of kaizen: 5S: (seiri, seiton, seiso, seiketsu, and shitsuke) which is adapted to concise, neat, clean, clean, care and diligent. The communication barriers are cultural, educational, personal, and environmental. While the supporting aspects are the government's attention, the suitability of Hipmikindo's operational field with vocational education curriculum at the secondary level and business at higher institutions, as well as the many productive age levels whose livelihoods are in the non-formal sector.